The righteous in the Colombian armed conflict: Symbolic exchanges between Europe and Latin America for post-conflict - Tognato, Carlos (Sociedad y Economía, 2017)
In Colombia the struggle over historical memory has focused on the opposition between victims and perpetrators. Here, I will introduce a third figure, that of the “righteous in the Colombian armed conflict”, thereby recovering the category of the “righteous among nations”, which to date has been exclusively used with reference to the Jewish Holocaust. Taking this step will allow me, first, to introduce an innovative tool for the purpose of cicatrizing the torn civil fabric of societies like the Colombian that come out of long lasting conflicts and need to restart the formation of solidarity ties among citizens belonging to distinct social and political groups. Second, it will serve as a narrative tool to counter the effects of extreme polarization over the sustainability of civil discourse within the Colombian public sphere. Finally, it will provide an opportunity to reflect on the challenges that are inherent in certain symbolic exchanges between Europe and Latin America.